Improvement of Sepsis Prognosis by Ulinastatin: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Wang, Huifang; Liu, Bin; Tang, Ying; Chang, Ping; Yao, Lishuai; Huang, Bo; Lodato, Robert F.; Liu, Zhanguo (Frontiers in Pharmacology, 2019)
Background: Ulinastatin has been prescribed to treat sepsis. However, there is doubt regarding the extent of any improvement in outcomes to guide future decision making. The purpose of this study was to evaluate the effects of ulinastatin on mortality and related outcomes in sepsis patients. Methods: Thirteen randomized controlled trials and two prospective studies published before September 1, 2018, that included 1358 patients with sepsis, severe sepsis, or septic shock were evaluated. The electronic databases searched in this study were PubMed, Medline, Embase, and China National Knowledge Infrastructure (CNKI) for Chinese Technical Periodicals. Results: Ulinastatin significantly decreased the all-cause mortality {Odds Ratio (OR)=0.48, 95% confidence interval (CI) [0.35–0.66], p<0.00001, I2=13%}, APACHE II score {Mean Difference (MD)=-2.40, 95% CI [-4.37,-0.44], p=0.02, I2=66%}, and reduced the incidence of multiple organ dysfunction syndrome (MODS) (OR=0.3, 95% CI [0.18, 0.49], p<0.00001, I2=0%). Ulinastatin also decreased the serum levels of IL-6 (MD=-88.5, 95% CI [-123.97,-53.04], p<0.00001), TNF-α (MD=-56.22, 95% CI [-72.11,-40.33], p<0.00001) and increased the serum levels of IL-10 (MD=37.73, 95% CI [16.92, 58.54], p=0.0004). Ulinastatin administration did not lead to any difference in the occurrence of adverse events. Conclusions: Ulinastatin improved all-cause mortality and other related outcomes in patients with sepsis or septic shock. The results of this meta-analysis suggest that ulinastatin may be an effective treatment for sepsis and septic shock.